2003
DOI: 10.1152/jn.01088.2002
|View full text |Cite
|
Sign up to set email alerts
|

Orexin-A Depolarizes Nucleus Tractus Solitarius Neurons Through Effects on Nonselective Cationic and K+ Conductances

Abstract: The nucleus tractus solitarius (NTS) plays central roles in a number of autonomic functions including cardiovascular control. Orexin (ORX)-A is a 33-amino-acid peptide implicated in the central regulation of energy metabolism, sleep, and the cardiovascular system. Studies demonstrate the presence of ORX-immunoreactive axons and both OX(1)R (orexin receptor) and OX(2)R mRNA within NTS. In this study, whole cell patch-clamp recordings were obtained from NTS neurons in rat medullary slices. Current-clamp studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
47
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 39 publications
6
47
0
Order By: Relevance
“…34 At a cellular level, electrophysiological experiments reveal that orexin can modulate synaptic transmission in neurons of the dorsal motor nucleus of the vagus nerve and the nucleus tractus solitarius. 31,35 These findings are particularly pertinent to aneurysmal SAH, which is associated with the development of neurogenic pulmonary oedema, changes in blood pressure, heart rate and myocardial injury, 36 complications which are attributed to abnormal autonomic discharge.…”
Section: Discussionmentioning
confidence: 99%
“…34 At a cellular level, electrophysiological experiments reveal that orexin can modulate synaptic transmission in neurons of the dorsal motor nucleus of the vagus nerve and the nucleus tractus solitarius. 31,35 These findings are particularly pertinent to aneurysmal SAH, which is associated with the development of neurogenic pulmonary oedema, changes in blood pressure, heart rate and myocardial injury, 36 complications which are attributed to abnormal autonomic discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Hcrt/Orx-activated cation currents have also been reported in area postrema neurons (Yang and Ferguson 2002), nucleus tractus solitarius (Yang and Ferguson 2003), paraventricular hypothalamic neurons (Yang and Ferguson 2002), and locus coruleus (LC) neurons (Murai and Akaike 2005). However, the current reported in those neurons seems different in several respects.…”
Section: Mechanisms Mediating Hcrt/orx-induced Depolarization In Dr Amentioning
confidence: 99%
“…These cells have a different function from the LC neurons and may relate more to control of vegetative and homeostatic processes, potentially linking the enteroceptive cells of the gut with the LH. The A2 cells of the nucleus of the solitary tract project to the LH area, and cells of the nucleus of the solitary tract show excitatory responses to hypocretin (Smith et al, 2002;Yang and Ferguson, 2003). Studies combining tract-tracing with immunostaining have shown a very specific innervation of subregions of the hypothalamic paraventricular nucleus by different catecholamine projections (Sawchenko and Swanson, 1982;Cunningham and Sawchenko, 1988).…”
Section: Functional Importance Of Ne Inhibition Of the Hypocretin Aromentioning
confidence: 99%